Study on static properties and mechanism of basalt fibre reinforced cement cured red sandstone soil - Yao Long; Jun-Hua Chen; Jie-Jie Mu; Qi-Yun Wang (PLoS ONE, 2025)
To enhance the suitability of red sandstone as a railway roadbed fill, basalt fiber (BF) was utilized to modify cement cured red sandstone soil. The study commenced with the determination of the optimal cement admixture in improved red sandstone soil through disintegration testing. Following this, unconfined compressive strength (UCS) tests, undrained and unconsolidated shear (UU) tests were conducted to assess the impact of BF on the strength and deformation characteristics of the cement cured red sandstone soil. Finally, the intrinsic and damage mechanisms through which BF improves the mechanical properties of cement cured red sandstone soil were elucidated in conjunction with scanning electron microscopy (SEM) testing. The results of the study indicate that cement significantly enhances the water stability of red sandstone soil. The disintegration of the specimens effectively ceased once the cement dosage exceeded 4%. The addition of BF significantly enhances the strength of cement cured red sandstone soil. As the BF content increases, the UCS and peak deviatoric stress exhibit an initial increase followed by a decrease. At the optimal BF dosage of 6‰, the UCS improved 24.48% ~ 25.40%, while the peak deviatoric stress improved 31.13% ~ 39.48%. The incorporation of BF also enhanced the deformation and stability properties of the cement cured red sandstone soil, resulting in increased elastic modulus and failure strain. However, the soil brittleness index exhibited varying degrees of reduction, while ductility was improved. The SEM test results indicate that cement primarily provides cohesion between soil particle. BF effectively inhibits the generation and propagation of cracks through the adhesive properties of cement and its interfacial friction with soil particle, as well as by forming a three-dimensional reinforcing network. The research result demonstrates that the use of BF to enhance cement-cured red sandstone soil significantly improves its mechanical properties, offering a sustainable method for strengthening railway foundations and contributing to advancements in civil engineering applications.